2020
DOI: 10.1038/s41467-020-18745-6
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted scavenging of extracellular ROS relieves suppressive immunogenic cell death

Abstract: Immunogenic cell death (ICD) and tumour-infiltrating T lymphocytes are severely weakened by elevated reactive oxygen species (ROS) in the tumour microenvironment. It is therefore of critical importance to modulate the level of extracellular ROS for the reversal of immunosuppressive environment. Here, we present a tumour extracellular matrix (ECM) targeting ROS nanoscavenger masked by pH sensitive covalently crosslinked polyethylene glycol. The nanoscavenger anchors on the ECM to sweep away the ROS from tumour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
161
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 39 publications
1
161
0
1
Order By: Relevance
“…In addition, many problems in tumor metastasis and drug resistance urgently need solved. An immunosuppressive ECM impedes the implementation of effective immunotherapies (154). These cancer therapy obstacles require an advanced NP system that can precisely target the molecular determinants of the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many problems in tumor metastasis and drug resistance urgently need solved. An immunosuppressive ECM impedes the implementation of effective immunotherapies (154). These cancer therapy obstacles require an advanced NP system that can precisely target the molecular determinants of the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence that ROS can oxidize the danger signal HMGB1 released from dying cells and thereby neutralize its alarmin activity [ 98 ]. A recent study reported that targeted scavenging of extracellular ROS using a tumor ECM targeting nanomaterial can maintain the stimulatory activity of HMGB1 and restore ICD-induced antitumor immunity [ 99 ]. These studies suggest that the level and duration of ROS may determine whether or not ICD can occur and lead to effective antitumor immunity.…”
Section: The Impact Of Oxidative Stress On Immune Cells In the Tmementioning
confidence: 99%
“…Besides this direct pathway beginning with ER stress, an important role in ICD is played by reactive oxygen species (ROS), which, however, seem to be a double-edged sword in this process. On one hand, it has been proven that ROS-induced autophagy triggers ER stress [ 55 ], on the other hand, ROS oxidize HMBG-1 and weaken the function of T cells [ 56 ]. In general, ROS are needed for ICD induction, since antioxidants successfully impede ICD, but for the further flow of the ICD process, it is of benefit to remove them from the tumor microenvironment [ 54 , 56 ].…”
Section: Immunogenic Cell Death and Cgsmentioning
confidence: 99%
“…On one hand, it has been proven that ROS-induced autophagy triggers ER stress [ 55 ], on the other hand, ROS oxidize HMBG-1 and weaken the function of T cells [ 56 ]. In general, ROS are needed for ICD induction, since antioxidants successfully impede ICD, but for the further flow of the ICD process, it is of benefit to remove them from the tumor microenvironment [ 54 , 56 ]. To sum up, for ICD induction, ER stress-causing, and ROS-generating compounds must be sought.…”
Section: Immunogenic Cell Death and Cgsmentioning
confidence: 99%